2009
DOI: 10.1080/19439340903370477
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of a government social franchise model on perceptions of service quality and client satisfaction at commune health stations in Vietnam

Abstract: This study evaluates behavioural outcomes associated with a new approach - the government social franchise (GSF) model - developed to improve reproductive health and family planning (RHFP) service quality and capacity in Vietnam's commune health stations. A quasi-experimental design with a matched control group assessed GSF model effects on client perceptions of serviced quality and satisfaction. Survey data from 1181 users and potential users were collected at baseline, six months and 12 months after implemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…A quasi-experimental study of a government franchise program in Vietnam found that after the introduction of the franchise clients did not report an overall increase in quality, but did perceive improvements in staff attitude. At the community level, residents perceived improvements in both overall service quality and provider expertise [27]. Qualitative focus groups reported similar findings; clients in Myanmar perceived franchise clinics to be of higher quality, in particular offering safer drugs and more privacy [28] and in Vietnam reported improvements in the quality of staff and facilities after introduction of franchised services [29].…”
Section: Resultsmentioning
confidence: 67%
See 2 more Smart Citations
“…A quasi-experimental study of a government franchise program in Vietnam found that after the introduction of the franchise clients did not report an overall increase in quality, but did perceive improvements in staff attitude. At the community level, residents perceived improvements in both overall service quality and provider expertise [27]. Qualitative focus groups reported similar findings; clients in Myanmar perceived franchise clinics to be of higher quality, in particular offering safer drugs and more privacy [28] and in Vietnam reported improvements in the quality of staff and facilities after introduction of franchised services [29].…”
Section: Resultsmentioning
confidence: 67%
“…Quasi-experimental pre- and post-studies show increased client satisfaction at a government franchise in Vietnam [27], and a non-profit franchise in Nepal [30]. Analysis of cross-sectional exit interview data found no variation in overall levels of client satisfaction between franchised and non-franchised clinics in India and Pakistan [20], [25]; however in Pakistan, franchise clients were more satisfied with the range of contraceptive methods and services offered [20].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a growing body of research on social franchising interventions shows mixed results across a variety of outcomes (1,(6)(7)(8). Social franchising is associated with improvements in patient-reported quality-of-care indicators such as client satisfaction (9)(10)(11). However, there is a paucity of studies that comprehensively assess quality of care across multiple dimensions such as provider practice, provider knowledge and skills, and service availability (1,6).…”
Section: Introductionmentioning
confidence: 99%
“…Experiments with the government social franchise business model, 30 which increases service utilisation and patient perceptions of quality through branding and social marketing programmes, quality improvement, formalisation of user fees and staff incentive schemes have been successful in some CHS system trials in Viet Nam. 31,32 Revenues generated by user fees can be used to improve and sustain service quality. Both the poor who need subsidies and those who are better off will benefit from higher quality services offered at their local CHS as a result of such initiatives.…”
Section: Policy Implications and Conclusionmentioning
confidence: 99%